Estudo caso-controle para identificar fatores de risco associados à sorologia anti-hcv reagente em homens presos em penitenciárias do Estado do Paraná, Brasil - Silva, Tania Maria Pazin Marques (2019)
The Brazilian prison system presents serious problems related to the increasing the number of prisoners and becomes more intense in the control of the hepatitis C virus (HCV). The control of HCV is highlighted due to the fact that the incarcerated population is considered a high risk group for contagious diseases because the favorable conditions found in prison for spreading these morbidities.The main purpose of this study was to identify features associated with hepatitis C infection among male prisoners in the prison system (correctional institutions) of Paraná, Brazil.We led a case-control study from March to May 2018.Twenty-seven cases and 54 matched controls participated as they belonged to the same penitentiary, age of 3 years more or less than the case;time of imprisonment of 5 years for more or less than the case of eleven penitentiaries of Paraná. The cases were defined as any prisoner with reactive serology for HCV. Controls were selected from male prisoners with serologic marker for non-reagent HCV. The variables analyzed were: race, marital status, schooling, occupation, number of times arrested, sentencing time, STD history, hepatitis knowledge, blood transfusion, tattooing, piercing, illicit drugs, injecting drugs, condom use, alcoholic beverage, sexual orientation, homosexual relationship and intimate visit. Univariate analysis and logistic regression model were performed to assess the likely risk factors for acquiring infection by hepatitis C virus. Logistic regression analysis showed that illicit drugs (odds ratio = 4.00, 95% CI, 1.06 - 15.08) and injectable drugs (odds ratio = 4.00; 95% confidence interval, 1.41-11.35) were the main risk factor for the acquisition of hepatitis C virus infection. This is the first case-control study reported with male prisoners in the closed prison system of Paraná, Brazil.This study provides evidence that HCV infection is associated with drug use by this population.